Welfare-Maximising Investors? – Utility Firm Performance with Heterogeneous Quality Preferences and Endogenous Ownership - Richard Meade; Magnus Soderberg (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
We model the endogenous ownership of a monopoly utility by either investors or the firm's customers. Ownership arises endogenously based on customers' quality preference, which affects each ownership type's viability. Customer ownership arises when quality preference falls below the threshold for profitable entry by investors, but above that for entry by customer-owners. When quality preferences diverge sufficiently, a profitmaximising investor-owned utility produces higher welfare than a welfare-maximising customer-owned firm, despite its higher prices. Otherwise, a customer-owned utility produces greater efficiency, quality and welfare, despite having lower-value customers. These predictions agree with empirical findings for US utilities, and find direct support using data from Electricity Distribution Businesses in New Zealand. To reflect ownership endogeneity, we instrument for ownership changes using the staggered rollout of regional air quality regulations. Our findings suggest that performance comparisons of customer- and investor-owned utilities should account for ownership endogeneity. This has implications for ownership debates, efficiency study specification, and the development of regulatory screens.
Keywords: D24; L15; L51; L94; P13; 330; Utilities; Price; Efficiency; Quality; Welfare; Ownership